An evaluation of the quality, suitability and impact on equity of clinical practice guidelines relevant to preterm birth for use in Aotearoa New Zealand - Briar Hunter; Lisa Dawes; Makayla Wadsworth; Lynn Sadler; Liza Edmonds; Judith McAra-Couper; Tina Allen-Mokaraka; Katie M. Groom (BMC Pregnancy and Childbirth, 2024)
Abstract Background Preterm birth is a leading cause of perinatal morbidity and mortality and a defining event for pregnant people, infants, and whānau (extended families). Recommendations have been made for a national preterm birth prevention initiative focusing on equity in Aotearoa New Zealand, including the development of a national best practice guide. An understanding of the number and quality of guidelines, and consideration of their suitability and impact on equity is required. Methods Guidelines were identified through a systematic literature search, search of professional bodies websites, and invitation to regional health services in Aotearoa New Zealand. Obstetric and midwifery clinical directors were invited to report on guideline use. Identified guidelines were appraised by a 23-member trans-disciplinary Review Panel; quantitatively using the AGREE-II instrument and qualitatively using modified ADAPTE questions. The quality of guidelines available but not in use was compared against those in current use, and by health services by level of maternity and neonatal care. Major themes affecting implementation and impact on equity were identified using Braun and Clarke methodology. Results A total of 235 guidelines were included for appraisal. Guidelines available but not in use by regional health services scored higher in quality than guidelines in current use (median domain score Rigour and Development 47.5 versus 18.8, p < 0.001, median domain score Overall Assessment 62.5 versus 44.4, p < 0.001). Guidelines in use by regional health services with tertiary maternity and neonatal services had higher median AGREE II scores in several domains, than those with secondary level services (median domain score Overall Assessment 50.0 versus 37.5, p < 0.001). Groups identified by the Review Panel as experiencing the greatest constraints and limitations to guideline implementation were rural, provincial, low socioeconomic, Māori, and Pacific populations. Identified themes to improve equity included a targeted approach to groups experiencing the least advantage; a culturally considered approach; nationally consistent guidance; and improved funding to support implementation of guideline recommendations. Conclusions We have systematically identified and assessed guidelines on preterm birth. High-quality guidelines will inform a national best practice guide for use in Taonga Tuku Iho, a knowledge translation project for equity in preterm birth care and outcomes in Aotearoa.